Assessment of Different Urinary Protein Precipitation Methods for Protein Profiling by Mass Spectrometry - Shantaram, Manjula (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: Urine has become one among the foremost engaging bio-fluids in clinical proteomics because is to often obtained non-invasively in massive quantities and is stable compared to other bio-fluids. The study is mainly focused to determine the best method for urinary protein extraction. Materials and Methods: Urinary proteins were precipitated using; chloroform/methanol, acetone, and TCA/acetone solvents followed by liquid chromatography– mass spectrometry (LC-MS) analysis. Results: In the present study, we have tested three different methods for urine protein precipitation and qualitatively evaluated by LC-MS-analysis. The protein samples were prepared using acetone, TCA/acetone, and M/C precipitation showed 51, 86, and 114 proteins, respectively. Of the percentage of identified proteins by mass spectrometric analysis revealed that about 17.6% of proteins were found in all the three methods. The highest percentage of shared proteins was observed between acetone and M/C precipitation (69%), followed by 63.8% and 52.7% in TCA/acetone and M/C and TCA/acetone precipitation methods, respectively. By contrast, M/C, TCA/acetone, and acetone precipitations showed 26%, 11.7%, and 12.4% of the unique proteins excluding shared proteins, respectively. The comparison between two different methods, acetone, and M/C, showed the highest percentage of shared protein as 69%, TCA/acetone and M/C precipitation showed 63.8%, and acetone and TCA/acetone precipitation showed 52.7%. M/C, TCA/acetone, and acetone precipitations showed 26%, 11.7%, and 12.4% of the unique proteins excluding shared proteins, respectively. Conclusion: This study contributes to establish a standard procedure in urine proteomics. Using urine biomarkers, it can be widely used in urine proteomics not only for diagnosis but also in basic biomedical research, such as physiology and pharmacology.